In-Law Relationships in Evolutionary Perspective: The Good, the Bad, and the Ugly - Daly, Martin; Perry, Gretchen (Frontiers in Sociology, 2021)
In-laws (relatives by marriage) are true kin because the descendants that they have in common make them "vehicles" of one another's inclusive fitness. From this shared interest flows cooperation and mutual valuation: the good side of in-law relationships. But there is also a bad side. Recent theoretical models err when they equate the inclusive fitness value of corresponding pairs of genetic and marital relatives - brother and brother-in-law, daughter and daughter-in-law - partly because a genetic relative's reproduction always replicates ego's genes whereas reproduction by an affine may not, and partly because of distinct avenues for nepotism. Close genetic relatives compete, often fiercely, over familial property, but the main issues in conflict among marital relatives are different and diverse: fidelity and paternity, divorce and autonomy, and inclinations to invest in distinct natal kindreds. These conflicts can get ugly, even lethal. We present the results of a pilot study conducted in Bangladesh which suggests that heightened mortality arising from mother-in-law / daughter-in-law conflict may be a two-way street, and we urge others to replicate and extend these analyses.